-7x-12=-9

Simple and best practice solution for -7x-12=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x-12=-9 equation:


Simplifying
-7x + -12 = -9

Reorder the terms:
-12 + -7x = -9

Solving
-12 + -7x = -9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -7x = -9 + 12

Combine like terms: -12 + 12 = 0
0 + -7x = -9 + 12
-7x = -9 + 12

Combine like terms: -9 + 12 = 3
-7x = 3

Divide each side by '-7'.
x = -0.4285714286

Simplifying
x = -0.4285714286

See similar equations:

| 2x+5+3x=25 | | 28x^2-3x-1=0 | | 49x^2+70x+25= | | 2t^5-14t^4+20t^3= | | 2t^5-14t^4+20t^4= | | x^2+10x-224=0 | | (x-4)(x+9)=0 | | (2u+18)(u^2-9)=0 | | 2.5x+0.25x=1.25+x | | x^5-11x^4-26x^3= | | 4x-7=8+2x | | 4x^2+32x-80= | | 24-y=5y | | 4(a+3)=11 | | 0.21y-0.8=0.11y+1-0.8y | | t(t+5)=2t^2+7 | | (x+7)(x+7)=2x^2+13x+19 | | 5m-26=-25+6m | | 5x^2-40x^2+75x= | | 3(5x+1)+6(5x+1)=2 | | .8m-.2m=9 | | 2x^4-3x^3+2x^2-15x+14=0 | | u^2-6u+8=0 | | -32xy^5+40x^3y^5-16xy^5= | | 8y=7y-45 | | 3t^3-9t+6=0 | | 27c^4-125c=0 | | 9x^2-5x=3 | | -8=-x-4 | | 3x=2-4y | | 10y=5y-5 | | 4(3x+4)=52 |

Equations solver categories